2011
DOI: 10.1186/1741-7007-9-87
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of endosymbiosis within the Enterobacteriaceae (γ-Proteobacteria): convergence of complex phylogenetic approaches

Abstract: BackgroundThe bacterial family Enterobacteriaceae gave rise to a variety of symbiotic forms, from the loosely associated commensals, often designated as secondary (S) symbionts, to obligate mutualists, called primary (P) symbionts. Determination of the evolutionary processes behind this phenomenon has long been hampered by the unreliability of phylogenetic reconstructions within this group of bacteria. The main reasons have been the absence of sufficient data, the highly derived nature of the symbiont genomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 139 publications
(140 reference statements)
2
104
1
Order By: Relevance
“…Nevertheless, its phylogenetic placement has to be considered with caution, because of long-branch attraction. As already observed by Husník et al (2011), the monophyly of the cluster formed by Sodalis, Baumannia, Blochmannia and Wigglesworthia, in which Westeberhardia appears, needs to be further tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, its phylogenetic placement has to be considered with caution, because of long-branch attraction. As already observed by Husník et al (2011), the monophyly of the cluster formed by Sodalis, Baumannia, Blochmannia and Wigglesworthia, in which Westeberhardia appears, needs to be further tested.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Wolbachia, we identified six scaffolds of an unknown Enterobacteriaceae. Following de novo genome assembly and annotation (see below), we used translated CDS sequences for phylogenetic placement following Husník et al (2011). Briefly, we performed Dayhoff6 recoding followed by a phylogenomic reconstruction with PhyloBayes v.3.3f (Lartillot et al, 2009), based on 64 single-copy protein clusters (Supplementary Information).…”
Section: Westeberhardia Detection and Phylogenomic Analysesmentioning
confidence: 99%
“…occasionally acquired from surrounding environments (or bacteria that contaminated insects) and that provided benefits to the host (53,54). In this context, the symbiotic association found in C. saccharivorus may represent an intermediate stage from the evolutionarily primitive gut symbiosis from environmental transmission to the sophisticated association maintained by vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the progressive removal of these positions violating the assumption of homogeneity PHILIPPE H. et al, Pitfalls in supermatrix phylogenomics 17 of the CAT mixture model (Lartillot & Philippe 2004) led to a single topological change: the recovery of the more classical sister-group relationship between cnidarians and bilaterians. Similarly, the gammaproteobacterial endosymbionts of insects have an AT-rich genome and tend to be artificially clustered in trees based on nucleotide sequences Husník et al (2011). By progressively removing the positions that were the most compositionally biased (i.e., a position only containing A and T, or G and C, is unbiased), Husník et al (2011) were able to overcome this composition-based artefact and to recover a tree identical to the one obtained from amino-acid sequences.…”
mentioning
confidence: 87%
“…Similarly, the gammaproteobacterial endosymbionts of insects have an AT-rich genome and tend to be artificially clustered in trees based on nucleotide sequences Husník et al (2011). By progressively removing the positions that were the most compositionally biased (i.e., a position only containing A and T, or G and C, is unbiased), Husník et al (2011) were able to overcome this composition-based artefact and to recover a tree identical to the one obtained from amino-acid sequences. Finally, recent studies of genome datasets in mammals (Romiguier et al 2013) and birds (Jarvis et al 2014) have revealed that AT-rich genes hold a much clearer phylogenetic signal than GC-rich genes, which are subjects to GC-biased geneconversion (Eyre-Walker 1993) episodes possibly leading to an increased heterogeneity in both base composition and evolutionary rate among taxa.…”
mentioning
confidence: 87%